HUBUNGAN PERSEPSI KEGANASAN KANKER PAYUDARA DENGAN PRAKTIK SADARI (PERIKSA PAYUDARA SENDIRI) PADA MAHASISWI FAKULTAS KESEHATAN MASYARAKAT UNDIP SEMARANG - Nur Afifah Azhari; Dharminto Dharminto; Sri Winarni; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2021)
Breast Self-Examination (BSE) is one of the most important methods for early diagnosis of breast cancer. Generally, Student of Public Health have obtained information about breast cancer and BSE so they tend to have good knowledge. But in fact their awareness to do Breast Self-Examination is still low (30%). The purpose of this study is to determine the relationship between severity of breast cancer perception based on patient survival, treatment costs, and perceived suffering with breast self-examination practice (BSE) in female student at the Faculty of Public Health Diponegoro University Semarang. This research is a quantitative research with explanatory research method and cross sectional study design. The population in this study was 1166 female students with a sample of 102 respondents taken using a simple random sampling technique. The results showed that most of the respondents were at the age of 19 years (33,3%), and were Grade 1/Class 2019 students and Level 3/Class 2017 students (27,5%). Correlation test results show there is a weak positive relationship between patient survival sub-variables (p-value = 0.010, r=0,256) and perceived suffering (p-value = 0.019, r=0,231) with BSE practices in female students. Therefore the perception of severity based on breast cancer survivors has an important role in the practice of BSE. It is recommended for female students to increase their awareness of their health by paying more attention to the state of their breasts and increasing their understanding of BSE well.